Transition Cow Metabolites and Physical Traits Influence Days to First Postpartum Ovulation in Dairy Cows - S. Banuelos; J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to assess key metabolites and patterns of prepartum and postpartum physical activity as they relate to the onset of first postpartum ovulation in lactating dairy cows. Close-up dry Holstein cows (n = 82) and late gestation heifers (n = 78) were enrolled beginning 3 weeks before expected calving date (day 0). Cows were fit with Cow SensOor ear tags to assess transitional changes in eating, resting, rumination, activity, and ear-surface temperatures. Rectal temperatures were assessed and blood samples were collected on days 0, 3, 7, and 14 to measure concentrations of glucose, free fatty acids (FFA), β-hydroxybutyrate (BHB), calcium, and haptoglobin (measure of inflammation). Body condition scores (BCS) and body weights (BW) were measured weekly, and blood samples were collected weekly from 3 through 10 weeks after calving to quantify changes in progesterone to detect luteal function after ovulation. Cows first ovulating before median day 33 were classified as early (n = 76), whereas those first ovulating after day 33 were classified as late (n = 84). Early ovulating cows first ovulated earlier than the late ovulation cows. Compared with late ovulating cows, early ovulating cows had lesser concentrations of FFA, BHB, and haptoglobin on days 0, 3, 7, and 14 in addition to having lower rectal temperatures and ear-surface temperatures. Ear-surface temperatures began to decrease 4 days before parturition and remained less after calving than cows that subsequently ovulated late. Early ovulating cows tended to spend more time eating, and less time resting and being active during the first 3 weeks after calving, and lost less BW and BCS during the first 9 weeks compared with late ovulating cows. Although no differences were detected in yields of milk or energy-corrected milk during the first 9 weeks after calving, early compared with late ovulating cows produced more milk protein. We concluded that metabolic measures during the first 2 weeks after calving, and physical and behavioral traits are associated with the onset of postpartum ovarian activity.
Keywords: activity; behavior; dairy cow; postpartum ovulation; transition period